Study on maternal and perinatal outcome in eclampsia in a tertiary care hospital - Agrawal, Sippy; Pandey, Divya; Sharma, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Eclampsia is an unpredictable multi-organ disease unique to pregnancy and is largely a preventable condition, responsible for high maternal and perinatal mortality. Methods: The present study was conducted in the Department of Obstetrics and Gynaecology in Maharani Laxmi Bai Medical College, Jhansi. It was a retrospective study conducted over a period of 12 months on all eclamptic cases attending our hospital and feto-maternal outcome data was analysed. Results: The incidence of eclampsia in our hospital was 2.22%. Most of the eclamptic cases were antepartum eclampsia constituting 81.48%. During the study period there were a total of 2430 obstetric admissions out of which 54 were eclamptic cases. There were 89 near miss cases and 21 maternal deaths. 16 (17.97%) near miss cases and 7(33.33%) maternal deaths were due to eclampsia. 37.03% patients had complications. Pulmonary edema/ARDS was the most common complication seen in our study. Early neonatal mortality in our study was 11.11%, 11 new-borns needed NICU care. Prematurity was the most common cause. Conclusions: Adequate screening, monitoring and routine check-up during and after pregnancy may prevent worsening the maternal and foetal outcome. Lack of antenatal care is a common risk factor for eclampsia is and this needs to be addressed to prevent this serious complication of pregnancy.